Rapid evolution of virus sequences in intrinsically disordered protein regions. - Leonid Gitlin; Tzachi Hagai; Anthony LaBarbera; Mark Solovey; Raul Andino (PLoS Pathogens)
Nodamura Virus (NoV) is a nodavirus originally isolated from insects that can replicate in a wide variety of hosts, including mammals. Because of their simplicity and ability to replicate in many diverse hosts, NoV, and the Nodaviridae in general, provide a unique window into the evolution of viruses and host-virus interactions. Here we show that the C-terminus of the viral polymerase exhibits extreme structural and evolutionary flexibility. Indeed, fewer than 10 positively charged residues from the 110 amino acid-long C-terminal region of protein A are required to support RNA1 replication. Strikingly, this region can be replaced by completely unrelated protein sequences, yet still produce a functional replicase. Structure predictions, as well as evolutionary and mutational analyses, indicate that the C-terminal region is structurally disordered and evolves faster than the rest of the viral proteome. Thus, the function of an intrinsically unstructured protein region can be independent of most of its primary sequence, conferring both functional robustness and sequence plasticity on the protein. Our results provide an experimental explanation for rapid evolution of unstructured regions, which enables an effective exploration of the sequence space, and likely function space, available to the virus.